First fun animal encyclopedia - Parker, Steve (Miles Kelly Great Bardfield, 2004)
First Fun Animal Encyclopedia by Steve Parker is a vibrant and engaging introduction to the animal kingdom, filled with fascinating facts and colorful illustrations for young readers.